Efeito da actividade física na insuficiência venosa crónica dos membros inferiores. - Luiz Ronaldo Alberti; Andy Petroianu; Danielle Corrêa; Thiago Franco Silva (Acta Médica Portuguesa, 2008)
Chronic venous disease of the lower limbs is one of the most commonly reported medical conditions and a substancial source of morbidity. The aim or the present work was to assess the influence of the physical activity on chronic venous insufficiency of the lower limbs.This study was carried out by mean of interviews with 100 consecutive people randomly selected, of ages older than 50 years old of both genders, distributed into two groups: Group 1 (n = 50): people that practiced physical activity for more than two years, and Group 2 (n = 50): people without history of physical activities. All of them were identified by age and gender. Risk factors for chronic venous insufficiency, family history and past therapeutics were also assessed. The signs of chronic venous insufficiency were classified by the physical exam in: absent, mild and severe. The results were compared using Student's t test, chi-square test and Fisher's exact test. Odds ratio and confidence intervals were calculated as well. The significance was considered for values corresponding to p < 0.05.The women of Group 1 were not different from Group 2 (p > 0.05). 40% of the women and only 8% of the men in Group 1 were submitted to previous treatment (p = 0.008), whereas this incidence was 48% for the women and 4% for the man of the sedentary group. Family history of chronic venous disease was more frequent in the sedentary women (p = 0.01) than in the sedentary men. There was no difference among the presence of signs of chronic venous diseases among the sedentary individuals' group and the ones that practiced physical activity (p = 0.2067), so much for the women as for the men.According to this present work, there was no relationship between the practice of physical activity and the occurrence of chronic venous insufficiency of the lower limbs, however physical activity avoided the development of this disease to more severe stages.